THE ROLE OF TEACHERS IN LEARNING ARABIC VOCABULARY ON THE LEARNING OUTCOMES OF MAHARAH KALAM OF CLASS VII FEMALE STUDENTS AT MODERN PESANTREN UMMUL QURO AL-ISLAMI BOGOR - Maulana, Rizky (Program Studi Pendidikan Bahasa Arab, 2024)
This research is motivated by the observation that the role of teachers in teaching mufrodat is still relatively low. This study aims to understand the position of teachers in teaching mufrodat in class and its impact on students' maharah kalam learning outcomes, as well as to obtain accurate data. Using quantitative descriptive method. The study population was 7th grade students, with a saturated sample of 40 students. Data collection was conducted through questionnaires, documents, and interviews, while data processing used SPSS version 25. The results showed that the teacher's role in learning Arabic vocabulary increased by 68%, which was categorized as very good. The improvement of students' maharah kalam learning outcomes reached 40%, which was categorized as good. The conclusion of this study is that the improvement of maharah kalam of grade 7 students at Modern Pesantren Ummul Quro Al-Islami Bogor is significantly influenced by the role of teachers in learning Arabic vocabulary. The conclusion of this study is that student learning outcomes are not always influenced by the role of the teacher alone, but there are other inhibiting factors